2021
DOI: 10.1161/hypertensionaha.121.17797
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Blood Pressure Variability With Dementia and Cognitive Impairment: A Systematic Review and Meta-Analysis

Abstract: Research links high blood pressure variability (BPV) with stroke and cerebrovascular disease, however, its association with cognition remains unclear. Moreover, it remains uncertain which BP-derived parameter (ie, variability or mean) holds more significance in understanding vascular contributions to cognitive impairment. We searched PubMed, Embase, PsycINFO, and Scopus and performed a meta-analysis of studies that quantified the association between resting BPV with dementia or cognitive impairment in adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 115 publications
10
100
0
3
Order By: Relevance
“…Other recent studies on average BP 45 and BPV 15 reported associations with neurofibrillary tangles but not with amyloid plaques. Beyond vascular factors, changes in cognition are more strongly associated with longitudinal changes in CSF tau than in CSF Aβ, 44 even over a short period of time.…”
Section: Discussionmentioning
confidence: 75%
“…Other recent studies on average BP 45 and BPV 15 reported associations with neurofibrillary tangles but not with amyloid plaques. Beyond vascular factors, changes in cognition are more strongly associated with longitudinal changes in CSF tau than in CSF Aβ, 44 even over a short period of time.…”
Section: Discussionmentioning
confidence: 75%
“…A 2021 meta-analysis of 20 studies that involved 7.8 million participants showed that BPV had a stronger association with dementia and cognitive impairment than mean BP levels 85 . This finding was confirmed in a randomized trial showing that in old adults without major cognitive impairment, higher long-term, visit-to-visit BPV was associated with an increased risk of dementia and cognitive decline, independently of average BP levels and use of antihypertensive medication 86 .…”
Section: Clinical Relevance Of Bpvmentioning
confidence: 99%
“…Many studies have indicated that VVV is associated with cognitive impairment 6 and poses a risk of the development of dementia. 7 Cerebral small‐vessel disease was suggested to be a pivotal pathophysiology. 8 …”
mentioning
confidence: 99%